2017
DOI: 10.1152/japplphysiol.00154.2017
|View full text |Cite
|
Sign up to set email alerts
|

Treating fructose-induced metabolic changes in mice with high-intensity interval training: insights in the liver, white adipose tissue, and skeletal muscle

Abstract: Fructose-rich caloric sweeteners induce adverse changes in the metabolism of humans. The study evaluated the effects of high-intensity interval training (HIIT) on a fructose feeding model, focusing on the liver, white adipose tissue (WAT), skeletal muscle, and their interplay. Male C57BL/6 mice were fed for 18 wk one of the following diets: control (C; 5% of total energy from fructose) or fructose (F; 55% of total energy from fructose). In the 10th week, for an additional 8-wk period, the groups were divided i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 52 publications
1
5
0
2
Order By: Relevance
“…With respect to skeletal muscle, we have previously shown that 4-weeks of aerobic exercise can enhance skeletal muscle mitochondrial biogenesis and function in male mice [49]. Motta et al [50] also showed that HIIT ameliorated fructose-induced metabolic dysfunction in male mice through mitochondrial biogenesis and β-oxidation, via irisin and PGC1 α in skeletal muscle. Moreover, several recent trials have demonstrated that 3–12 weeks of HIIT can significantly increase resting metabolic rate [51] and post-exercise oxygen consumption in healthy adults [52], and fat oxidation in obese adolescents [53].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to skeletal muscle, we have previously shown that 4-weeks of aerobic exercise can enhance skeletal muscle mitochondrial biogenesis and function in male mice [49]. Motta et al [50] also showed that HIIT ameliorated fructose-induced metabolic dysfunction in male mice through mitochondrial biogenesis and β-oxidation, via irisin and PGC1 α in skeletal muscle. Moreover, several recent trials have demonstrated that 3–12 weeks of HIIT can significantly increase resting metabolic rate [51] and post-exercise oxygen consumption in healthy adults [52], and fat oxidation in obese adolescents [53].…”
Section: Discussionmentioning
confidence: 99%
“…found liver steatosis develops with adipocyte hypertrophy, and these detrimental events were relevant to altered gene expressions including FNDC5 , PGC1α and PGC1β , all of which were efficiently prevented upon high-intensity interval training (HIIT) (Ref. 37). The authors concluded that the beneficial influences of HIIT, in parallel to the medicinal properties of metformin, may partially alleviate the liver injury and prevent progressive NAFLD from more advanced pathological stages.…”
Section: Association Between Fndc5/irisin and Nafld (And Relevant Met...mentioning
confidence: 99%
“…Segundo Motta, et al (2017) um estudo avaliou os efeitos de treinamento de alta intensidade intervalado (HIIT) em um modelo alimentar com frutose. Ratos machos foram alimentados por 18 semanas com as seguintes dietas: controle (C: 5% do total de energia com fructose), frutose (F: 55% do total energético de frutose).…”
Section: Dhgna E Exercícios Resistidosunclassified